Theoretical assessment of biomethane production from algal residues after biodiesel production. Issue 1 (13th October 2017) - Zhu, Liandong; Li, Zhaohua; Hiltunen, Erkki
Abstract : Energy shortage, global warming, and climate changes call for the creation and breakthroughs of renewable and sustainable energy technologies, and thus biofuels from microalgae have been the object of ever‐increasing interest. Microalgal biodiesel production presents as one of the promising options for biofuel production, since most microalgal species contain rich lipids. However, large amounts of residues are left behind after microalgal biodiesel production. In an effort to improve the potential economics of microalgal biofuels, it is essential to make full use of microalgal post‐extracts. This Focus Article determines the theoretical yields of microalgal biodiesel and biomethane together with the relevant calorific values during the continuous production. Based on the investigated species, the microalgal biodiesel and biomethane yields widely range from 6 to 134 g/kg‐VS and from 0.24 to 0.63 L/g‐VS, respectively, while the total calorific values experience the range of between 6.88 and 18.80 MJ/kg‐VS. Microalgal biodiesel production is not always required before anaerobic digestion, especially for those microalgal species with low lipid contents. Net energy ratio and cost‐effectiveness analysis are highlighted in order to evaluate the viability of the biorefinery process. Well‐funded research and development programs can help develop technologies and policies, thus driving the industry toward prosperity. WIREs Energy Environ 2018, 7:e273. doi: 10.1002/wene273. This article is categorized under: Bioenergy > Science and Materials Bioenergy > Systems and Infrastructure Abstract : Substance flow during the continuous production of biodiesel and biomethane.